Methotrexate treatment of squamous-cell head and neck cancers: dose-response evaluation. Issue 6264 (21st February 1981) - Woods, R L; Fox, R M; Tattersall, M H
Abstract : Seventy-two patients with advanced squamous-cell carcinomas of the head and neck were randomised to receive weekly intravenous methotrexate at doses of either 50 mg/m2 (low dose), 500 mg/m2 (medium dose), or 5 g/m2 (high dose). Patients who failed to respond after four treatments at their initial dose were given four further treatments at the next higher dose. There were two complete responses and 21 partial responses to the initial dose--in 10 out of 22 patients given the high dose, seven out of 27 given the medium dose, six out of 23 given the low dose. A further five out of 16 patients responded after crossing over to a higher dose. Toxicity was more severe with the high-dose regimen. Responders survived significantly longer than non-responders (p less than 0.05), but there was no significant difference in durations of survival among the three treatment groups. Analysis of patients who completed the first four treatments indicated an improved response rate and duration of survival for the high-dose group. Because of toxicity associated with high-dose methotrexate this treatment produces no overall greater benefit than low-dose regimens.